2021
DOI: 10.14814/phy2.14930
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ketones and mental fatigue in high fat‐induced obese and non‐obese rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The NOR test is used as a measure of short-term episodic memory, and we have previously used this test to show acute i.c.v administration of soluble amyloid β oligomers caused robust and enduring deficits ( Watremez et al, 2018 ). In line with the published literature, we found that 4 weeks of high-fat feeding results in cognitive impairment in Sprague Dawley rats ( Niepoetter et al, 2021 ). Hence, we injected the shRNA construct targeting CMKLR1 into rats after 4 weeks of high-fat feeding.…”
Section: Discussionsupporting
confidence: 92%
“…The NOR test is used as a measure of short-term episodic memory, and we have previously used this test to show acute i.c.v administration of soluble amyloid β oligomers caused robust and enduring deficits ( Watremez et al, 2018 ). In line with the published literature, we found that 4 weeks of high-fat feeding results in cognitive impairment in Sprague Dawley rats ( Niepoetter et al, 2021 ). Hence, we injected the shRNA construct targeting CMKLR1 into rats after 4 weeks of high-fat feeding.…”
Section: Discussionsupporting
confidence: 92%
“…ANOVA of individual variables. Measurements of body weight, blood glucose and ketones as well as the behavioral data analysis during DIO is previously published [34]. In this study, body weight, blood glucose, and blood ketones were measured once per week and the averages of each of these variables analyzed using a repeated measures analysis of variance (ANOVA) in PROC MIXED of SAS (version 9.4).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining IEIs occurred at 24-hours (one day), 72 hours (3 days), and 168-hours (7 days) after the initial 0-hour test. The duration spent by the rats investigating the new object compared to the familiar object translates to the animal’s recognition and provides a numerical measurement for memory [ 34 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent proof indicates a linear relationship between obesity and cognitive deficits, and an increased risk of dementia and Alzheimer's disease (AD) later in life as well (Solas et al, 2017). Studies in animal models of obesity have shown that SD rats exhibit impaired learning and cognitive function with decreased neuronal and myelin viability after high-fat dietary feeding (Niepoetter et al, 2021). Previous literature has reported that the development of obesity-related cognitive impairment may be associated with inflammation, insulin resistance, disruption of the blood-brain barrier, and abnormal endocrine function, but more precise mechanisms need to be researched (Solas et al, 2017;Niepoetter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%